As formas de referência ao sujeito de 2ª pessoa do singular em missivas mineiras dos séculos XIX e XX: uma análise linguístico-social - Erenildo Queiroz de Souza (2021)
The objective of this research is to describe the forms of reference to the 2SG subject (vossa mercê, você, tu) correlated to the social relations that underlie them in the handwritten letters of Minas Gerais in the 19th and 20th centuries, based on the Theory of Power and Solidarity (BROWN & GILMAN, 1960), the theoretical-methodological assumptions of historical Sociolinguistics (HERNÁNDEZ-CAMPOY & CONDE SILVESTRE, 2012; HERNÁNDEZ-CAMPOY & SHILLING, 2012) and Labovian Sociolinguistics (WEINREICH, LABOV & HERZOG, 2008 [1968]; LABOV, 1994). It is based on the hypothesis that você would be more productive than tu, according to Lopes & Rumeu (2015), Rumeu, Cruz & Cardoso (2018). One seeks to know at what level of variation você and tu would be in the writing of past synchronies and how the relationships of Power and Solidarity would be expressed. The starting point of this research is the understanding that the syntactic function of the subject represents the main gateway assumed by grammatical pronouns such as você and a gente, when inserted in the pronominal system of Brazilian Portuguese as already observed in diachronic studies (RUMEU, 2013; SOUZA, 2012; LOPES & CAVALCANTE, 2011; LOPES & VIANNA, 2012). This research takes the present as the basis for the reconstruction of the path traveled by linguistic change in the past (LABOV, 1994) based on 332 personal letters (loving, familiar and friendship letters) and 26 trade letters available in public and personal collections. The results of “vossa mercê” (“You”), “você” and “tu” (“You) are distributed in relation to the expression of the form of reference to the subject of 2SG (null/full), the verbal person (concordance), the formal and semantic parallelism, the gender of the letter, the gender of the informant, the age, the interpersonal relationship, the social relations and the period of the letters. The data were submitted to RBrul for the generation of the percentage and probabilistic indexes of the variable rule under discussion: tu versus você. The results achieved were surprising in relation to the main hypothesis, considering that tu as a subject proved to be more productive than você in the analyzed letters from Minas Gerais, even in a fierce dispute. The verbal forms of 3SG (concordance), the você-subject (“you-subject”), the clitic forms of 3SG, the possessive of 3SG and the forms of the você non-subject (“you non-subject”) show themselves to be propellers of the “você” in the letters of Minas Gerais. Considering the interaction between interlocutors, tu and você were more productive in symmetrical social relations. This fact suggests the forwarding of Mineira society through the domains of Solidarity, whereas “vossa mercê” is shown to be restricted to ascending asymmetrical relations (from bottom to top) according to Lopes & Rumeu (2015).